Oxford handbook of clinical surgery (Oxford University Press, 1990)
This illustrated guide provides a concise review of current surgical practice and general operative surgery. It includes information on anatomy for surgeons, and general, plastic, vascular, pediatric, endocrine, and orthopedic surgery. Practice procedures and operative surgical techniques are described, as are important ethical and legal concerns. This unique book gives readers a succinct account of such non-traditional issues as surgery and contraceptives, stopping smoking before surgery, and surgery and mycardial infarction. Ideal for medical students, interns, and nurses, the volume provides a blank page for notes and annotations after each page of text, as well as many illustrations that help clarify the techniques and procedures presented. It is recommended for all health care professionals.